KENTLEŞME VE KENT MORFOLOJİSİ İLİŞKİLERİ: CEYHAN ÖRNEĞİ - ŞİNİK, METE (Fırat Üniveristesi, 2016)
Ceyhan kentleşmesi ile kent morfolojisi ilişki açıklanmaya çalışılmıştır. Çalışmada geçmişten günümüze kentin hem mekansal gelişimi hem de beşeri ve ekonomik ilişkileri arasında bağlar kurulmuştur.

Ceyhan urbanization, urban morphology and the relationship are discussed. Study from past to present established links between the city's spatial development both human and economic relations.
Urbanization and urban morphology relations: Example of Ceyhan
Keywords: Coğrafya